Potassium and zeolitic structure modified ultra-microporous adsorbent materials from a renewable feedstock with favourable surface chemistry for CO2 capture - LIU, Xin; Sun, Yuan; Liu, Jingjing; Sun, Chenggong; Liu, Hao; Xue, Qian; Smith, Emily F.; Snape, Colin E. (American Chemical Society, 2017)
Novel hierarchically structured microporous bio-carbons with exceptionally high capacities for CO2 capture have been synthesized from the abundant agricultural waste of rice husk (RH), using a facile methodology that effectively integrated carbonisation, activation and potassium intercalation into a one-step process. Textural characterisation demonstrates that the synthesized bio-carbons exhibit exceedingly high ultra-microporosity accounting for up to 95% of total porosity mainly as a result of the naturally occurring silicon compounds within the RH molecular framework structures. With a modest surface area of up to 1035 m2/g and a total pore volume of 0.43 cm3/g, the best performing RH carbon has showed exceptionally high and fully reversible CO2 uptake capacity of 2.0 mmol/g at 25 oC and a CO2 partial pressure of 0.15 bar, which represents one of the highest uptakes ever reported for both carbon and MOF materials usually prepared from using cost-prohibitive precursor materials with cumbersome methodologies. It has been found that up to 50% of the total CO2 uptake is attributable to the unique surface chemistry of the RH carbons, which appears to be dominated by the enhanced formation of extra-framework potassium cations owing to the exceedingly high levels of ultra-microporosity and the presence of zeolitic structures incorporated within the carbon matrices. Characterisations by EDX element mapping, XPS and the heat of adsorption measurements confirm the existence of a range of zeolitic structures, which essentially transforms the RH carbons into a kind of zeolite-carbon nanocomposite materials with strong surface affinity to CO2.